INTERACTIVE LEARNING. FEATURES OF THE POSITION OF TEACHERS AND STUDENTS - Revenko, V.V. (Pedagogy of Higher and Secondary Education, 2009)
In the article the author makes an attempt to substantiate the peculiarities of the teacher’s and the students’ positions in the process of interactive learning.